Improving Literacy Skills Through The Minimum Competency Assessment (AKM) In Class V Students At SD Negeri Triwung Kidul II Probolinggo City - Pramesti, Adella; Nafsiyah, Azizah Tun; Oktaviaji, Firda; Fitria, Lely Nur; Sriwijayanti, Ribut Prastiwi; Nazilah., Vita Rahmatun (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research was motivated by observation data which showed that the literacy skills of grade 5 students were quite low. The implementation of this activity aims to give students better thinking skills for various problems that arise in questions through AKM classes which are held in 2 sessions, namely AKM pre-test and Post-test. This research was carried out in class 5, attended by 18 students. This research is qualitative research which uses observation and interview methods. The research results show a significant increase in the implementation of class AKM. The increase in AKM scores for this class was supported by the successful implementation of the student work program. Skills have increased at the individual level and it is hoped that all students can achieve this, namely at a skilled or advanced competency level. From the pre-test to post-test AKM test activities there has been a good improvement as well as a fairly high increase in literacy skills among students. Researchers apply appropriate methods and implement work programs well. So it was successful in making students' post-test results improve from the previous test.